BIOGENIC SYNTHESIS OF COPPER NANOPARTICLES AND THEIR BIOLOGICAL APPLICATIONS: AN OVERVIEW - RAJU, SENTHIL KUMAR; KARUNAKARAN, ANANDAKUMAR; KUMAR, SHRIDHARSHINI; SEKAR, PRAVEEN; MURUGESAN, MARUTHAMUTHU; KARTHIKEYAN, MOHANAPRIYA (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Copper nanoparticles are one of the most promising agents in the field of nanotechnology which has the widest range of applications in various fields. Copper is an inorganic and safest material to humans, extensively used as an anti-bacterial, anti-fungal, anti-cancer agent and also as catalysts and sensors in high potential, peculiarly in nanosize. This emerged the preparation of CuNPs using various techniques. Many conventional methods have been employed for the synthesizing CuNPs which include electron beam lithography, inert gas condensation, ion implantation, laser ablation, mechanical milling, mechanical grinding, pulsed wire discharge, spray pyrolysis, vacuum vapour deposition, chemical reduction method, electrochemical method, microemulsion method, microwave method and solvothermal decomposition method. Relatively the biological method is highly recommended for the synthesis of CuNPs due to the absence of harmless chemicals, enhanced biocompatibility, eco-friendly, greater biological activity and low toxicity. This review is focussing on the biogenic synthesis of CuNPs using plants and micro-organisms, reaction conditions, characterization techniques and their applications.